Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given the function $$f (x) = x\bigg(x − {1\over4}\bigg)\bigg(x − {1\over2}\bigg)$$

How can I interpolate $f(x)$ with $p(x) = a_0T_0(x) + a_1T_1(x) + a_2T_2(x) + a_3T_3(x)$ to show that

$$a_0 = -{3\over8},\ \ a_1 = {7\over8},\ \ a_2 = −{3\over8},\ \ a_3 = {1\over4}$$

share|cite|improve this question
It may help if you define what each $T$ is. – Daryl Nov 13 '12 at 7:05
$T_k(x)$ are the Chebyshev polynomials, plus they cancel out when you do the integral – StealzHelium Nov 13 '12 at 7:18
up vote 0 down vote accepted

First, note that, the Chebyshev polynomials have the property

$$\int_{-1}^1 T_n(x)T_m(x)\,\frac{dx}{\sqrt{1-x^2}}= \begin{cases} 0 &: n\ne m \\ \pi &: n=m=0\\ \pi/2 &: n=m\ne 0 \end{cases}\rightarrow (*)\,.$$

The first four polynomials are $ T_0(x)=1, T_1(x)=x, T_2=2x^2-1, T_3=4 x^3-3x.$

Now, we have

$$ f(x) \sim a_0T_0(x) + a_1T_1(x) + a_2T_2(x) + a_3T_3(x) \rightarrow (1). $$

To find $a_i, i=0..3$, we exploit the above property. We start by finding $a_0$. Multiply both sides of $(1)$ by $T_0$ and integrate from $-1$ to $1$ w.r.t. the weight function $\frac{1}{\sqrt{1-x^2}}$ gives

$$ \int_{-1}^{1} \frac{f(x)T_0(x)}{\sqrt{1-x^2}}dx = a_0\int_{-1}^{1} \frac{{T_0}^2(x)}{\sqrt{1-x^2}}dx + a_1\int_{-1}^{1} \frac{{T_0}(x)T_1(x)}{\sqrt{1-x^2}}dx+\dots. $$

$$ \implies -\frac{3}{8}\pi = a_0 \pi + a_1.0 + a_2.0+a_3.0 \implies a_0=-\frac{3}{8} .$$

Notice that, we used the orthogonal property $(*)$ to evaluate the integrals on the right hand side in the above equation.

To find $a_1$, we multiply both sides of equation $(1)$ by $T_1$ and integrate from $-1$ to $1$ w.r.t. the weight function $\frac{1}{\sqrt{1-x^2}}$

$$ \int_{-1}^{1} \frac{f(x)T_1(x)}{\sqrt{1-x^2}}dx = a_0\int_{-1}^{1} \frac{{T_0}(x)T_1(x)}{\sqrt{1-x^2}}dx + a_1\int_{-1}^{1} \frac{{T_1}(x)T_1(x)}{\sqrt{1-x^2}}dx+\dots. $$

$$ \implies \frac{7}{16}\pi = a_0.0 + a_1\frac{\pi}{2}+a_2.0+a_3.0 \implies a_1 = \frac{7}{8}. $$

You can find the rest of $a_2$ and $a_3$ the same way.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.